155 Requirement of Mental-health Referral Letters for Staged and Revision Genital Gender-Affirming Surgeries: An Unsanctioned Barrier to Care. Issue 1 (1st April 2022) - Yuan, N.; Chung, T.; Ray, E.; Sioni, C.; Jimenez, A.; Garcia, M.
ABSTRACT: Introduction: The World Professional Association for Transgender Health (WPATH) recommends referral letters from two mental-health providers within one year of gender-affirming genital surgery (gGAS) to ensure patient readiness before primary surgeries. Many U.S. health-insurance plans will not authorize second- and third-stage surgeries or revision surgeries without two referral letters. Such requirements are not supported by WPATH guidelines. Objective: This study investigates insurance requirements for referral letters and their negative impact on care. Methods: We retrospectively reviewed all gGAS cases over a 4-year period at our tertiary care medical center. Referral-letter requirements for insurance authorization were documented. The nation's largest insurance companies, including commercial, state-, and federally funded plans, were contacted to confirm requirements. We prospectively recorded time needed to complete insurance authorization for a patient subset. WPATH publications were reviewed. Results: Nearly all reviewed U.S. health-insurance plans required annually updated referral letters for each gGAS procedure, including staged and revision surgeries. No updated letters changed clinical management. Referral-letter requirements delayed care. WPATH states that letters should not be needed for staged surgeries. Some plans required letters even for initial surgical consultation, a practice not supported by WPATH. Conclusions: Insurance companies' requirements for referral letters impede care and contradict WPATH guidelines. We advocate that referral letters should not be required for surgical consultations or for staged or revision surgeries after a patient has already had first-stage primary gGAS. Universal referral-letter requirements for secondary surgeries provide minimal clinical value, delay care, increase costs, and exacerbate gender dysphoria by invalidating gender transition. As with all procedures, surgeons themselves should be responsible for assessing patients' surgical readiness. Significant changes in mental-health status or social situation should prompt surgeons to seek reassessment. WPATH recommendations regarding referral letters should be clarified and consolidated into a single document. Disclosure: No